RNA and protein synthesis requirements for the resumption of meiosis in rabbit oocytes: the role of cumulus cells - Motlík, J; Fulka, J; Procházka, R; Rimkevicová, Z; Kubelka, M; Fulka, J (Reproduction, nutrition, development, 1989)
In vitro maturation of rabbit cumulus-enclosed oocytes was fully inhibited in alpha-amanitin- (100 micrograms/ml) and cycloheximide- (5 micrograms/ml) supplemented media. The inhibition was reversible and substantially reduced by delaying the addition of alpha-amanitin (2h) or cycloheximide (3 h). In contrast, both drugs did not inhibit germinal vesicle breakdown in denuded oocytes. Co-culture of granulosa cells (1 x 10(6)/ml) with denuded oocytes did not substitute for an intact cumulus. The data presented here suggest that the resumption of meiosis in rabbit cumulus-enclosed oocytes is dependent upon early transcriptional and translational events which probably occur within the cumulus cells.
Keywords: genetická transkripce; cykloheximid; RNA; Transcription, Genetic; Female; Meiosis; zvířata; oocyty; amanitiny; meióza; proteosyntéza; Cycloheximide; ženské pohlaví; ovariální folikul; králíci; Ovarian Follicle; Animals; Oocytes; Amanitins; Protein Biosynthesis; Rabbits